Interactions of Gum Depressants With Talc: Study of Adsorption by Spectroscopic and Allied Techniques (aa77a54c-5717-4f5a-be7a-06ed41804108) - P. Somasundaran; Z. Pan; D. R. Nagaraj; G. Anastassakis (International Mineral Processing Congress, 2003)
Gums are often used as depressants for talceous gangue minerals in the flotation of nickel and platinum bearing ores. However, the mechanisms of gum adsorption on talc are not clearly established. In this work, adsorption of guar gum at the talc-solution interface is investigated using spectroscopic and allied techniques. Guar gum adsorption on talc is not affected significantly by changes in solution conditions such as pH and ionic strength. Electrokinetic studies showed that guar gum decreased the negative zeta potential of talc but did not reverse the charge. Fluorescence spectroscopy studies conducted to investigate the role of hydrophobic bonding using pyrene and dansyl probes showed no evidence of the formation of hydrophobic domains at talc-aqueous interface. Urea, a hydrogen bond breaker, reduced the adsorption of guar on talc to the same extent as that for guar/alumina system, in which hydrogen bond plays an important role. All of the above results suggest that one of the main driving forces for guar adsorption on talc is hydrogen bonding rather than electrostatic or hydrophobic force.